S<span>tep-1 : Multiply the coefficient of the first term by the constant </span><span> <span> 3</span> • 4 = 12</span>
<span>Step-2 : Find two factors of </span> 12 <span> whose sum equals the coefficient of the middle term, which is </span><span> 13 </span><span>.
</span><span><span>
-12 + -1 = -13</span><span>
-6 + -2 = -8</span><span>
-4 + -3 = -7</span><span>
-3 + -4 = -7</span><span>
-2 + -6 = -8</span><span>
-1 + -12 = -13</span><span>
1 + 12 = 13 </span></span>
Answer:
Incorrect
Step-by-step explanation:
The angle is acute,which means under right triangle's usual size.
You need at least 90 cm to have a right triangle so no she is incorrect
All equations of lines must be wrote in the form: Y=mx+c
m= the gradient
c= y intercept
Y= 3x+2
Hope this helps!
Answer:
x^4 + 5x^3 - 12x^2 + 5x + 1